O prefácio de Deus: a estruturação do empíreo dantesco - Lucchesi, Marco Americo (1992)
Analysis of Dante's Empireo (canto XXX, XXI, XXXII and XXXIII from Paradiso). It is especially concentrated on the poetical relationship of its absolute transcendence, built on a labile hypersignificant text. The genesis of such hypersingn depends upon three elements: light, unity and transcedence: each of wich tries to accont for the superdetermination, the addition through wixh they are linked. The hypersingn does not identify itself with the divinity. It represents its textual space, the sum of icons, symbols and signs, whose effect makes up the mystery,k the arduous border between poetry and metaphysics, through the representation of the irrepressentable, in the hiatus between image and concept, establishing at last the dialetic of visibility and invisibility. Light, unity and transcedence organize in fact such dialetic. The objective of the Thesis, threfore, lies in the limits of the hyperuanian world, whose end is love.